Patterns of knowledge bases in large city regions in Germany: comparison of cores and their surrounding areas - Wagner, Madeleine; Growe, Anna (Geografiska annaler. Ser. B, Human geography, 2023)
Knowledge-intensive services are regarded as drivers of innovation and globalisation processes, and are mainly concentrated in large cities and metropolitan areas in the urban system. However, regionalisation processes of knowledge activities are increasing in the city-regional environment, which leads to a relief of the core cities and to an upgrading of the surrounding regions. The aim of this work was to present these regionalisation processes in the areas surrounding Germany’s 50 large city regions in terms of knowledge bases (analytical, synthetic, symbolic) for the period 2012-2019. The focus was on a differentiation of the large city regions into core areas and wider surrounding areas. Employment data from the Federal Employment Agency were used for the analysis. Firstly, we examined the change in importance of the core and wider surrounding areas in comparison to all large city regions in the German urban system in order to identify particular focal points of knowledge-economy development. Secondly, we looked at changes in the core and wider surrounding areas within the individual city regions in terms of different forms of knowledge. Finally, we argue for possible further theoretical developments regarding the importance of city-regional contexts in the field of knowledge-intensive services.
Online publiziert am 08. Nov. 2022
Gesehen am 19.09.2023